Pudhuvai Sivam: selected poems - Pudhuvai Sivam; SIVAM (Pudhuvai) (Pondicherry Pondicherry Institute of Liguistics and Culture, 2003)
Selected poems of a Tamil author.
Keywords: Indian English Poetry; Indian English Literature; Tamil Poetry Tr in English